Freaks: tra anormalità e deviazione. Nascite mostruose e fenomeni umani dall’uomo-gallina al circo di Barnum (Itinera, 2020)
The essay focuses on the theme of natural teratology, or the study of deformities, and above all on the positive figure of the freak, which I am going to analyze from a social and spectacular point of view. The analysis will go on probing the territories of the bizarre and the marvelous as presented by the Great American Museum of Barnum.
Keywords: Teratology, freak, abnormality, bizarre.